PERCEPTION OF SABAH AS A SAFE TOURIST DESTINATION FROM THE PERSPECTIVE OF THE TOUR OPERATORS AND TOURISTS - Pricilla Kuilis-Bosimin; Jennifer Kim Lian Chan (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This paper explores the perception of Sabah as a safe tourist destination and the key factors that influenced safety and security issues from the perspective of the tour operators and tourists. Qualitative research through semi-structured interviews were used to collect data from ten inbound tour operators registered with the Sabah Tourism Board and ten tourists who visited Sabah from January to March 2017. The findings indicated that most of the respondents perceived Sabah as a safe tourist destination and would not hesitate to revisit. The perception of safe destination was attributed to beautiful, friendly, haven and peaceful. A significant number of tourists perceived Sabah as a safe tourist destination due to the natural and pristine coastlines and natural environmental habitats. Sabah, well-known as the Land Below the Wind, has a beautiful feature with a wealth of natural paradise to offer to the tourists. Although several key incidents and unsafe events happened in Sabah, the general perception was that Sabah is a safe tourist destination and would not deter the tourists from visiting Sabah. The findings show that perception of Sabah as a safe tourist destination; in the sense that Sabah is described as a beautiful and peaceful tourist destination with friendly people around them and a haven to visit despite the incidents of kidnappings and crimes. Arising from the responses from the tour operators and the tourists, it was revealed that the key factors that influenced safety and security issues are described as human (illegal immigrants, intruders, lack of security personnel), activities (drug abusers, shootings), behavior (irresponsible people [tourists/visitors], negative perception), location (long and winding shores and unlit areas), crime (kidnappings, murder, thefts and threats) and animals (animal attacks)